Agile 2 : The Next Iteration of Agile /: The Next Iteration of Agile. (2021) - Berg, Cliff; Cagle, Kurt; Cooney, Lisa; Fewell, Philippa; Lander, Adrian; Nagappan, Raj; Robinson, Murray
No abstract available